Agronomic effects of biochar and wastewater irrigation in urban crop production of Tamale, northern Ghana - Akoto-Danso, Edmund K.; Manka’abusi, D.; Steiner, C.; Werner, S.; Häring, V.; Nyarko, G.; Marschner, B.; Drechsel, Pay; Buerkert, Andreas (Springer, 2018)
Agricultural production needs to increase, particularly in sub-Saharan Africa, many rural people are undernourished, and the urban population is growing rapidly. It is worrisome that on many West African soils with low cation exchange capacity and soil organic carbon content, mineral fertilization is rather inefficient. Under these conditions, wherever available untreated wastewater is used for irrigation despite the potential health risks to producers and consumers. For intensively cultivated soils with high mineralization rates, biochar application has been advocated as a promising management option. However, the agronomic benefits of wastewater reuse in agriculture and its interaction with biochar have received only limited attention. This study therefore investigated the effects of mineral fertilizer application and biochar amendment at two water quality and quantity levels on soil moisture, plant nutrition and biomass production on a Petroplinthic Cambisol over 2 years. Rice husk biochar applied at 20 t ha−1 significantly increased fresh matter yields in the first five cropping cycles by 15%, and by 9% by the end of 2 years. Compared with clean water, wastewater irrigation increased yields 10–20-fold on unfertilized plots during the dry seasons, while a fourfold increment was observed in the wet seasons. This seasonal difference is likely a result of the high sequence of irrigation events during the dry season. In this study, fertigation with wastewater contributed significantly to plant nutrition and nutrient recovery while yield-increasing biochar effects disappeared over time. Soil moisture was enhanced by up to 9% due to biochar amendments under unfertilized conditions.